2016
DOI: 10.1016/j.bbrep.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

‘Infertile’ studies on mitochondrial DNA variation in asthenozoospermic Tunisian men

Abstract: We reviewed five studies undertaken by the same research group on the possible links between mitochondrial DNA (mtDNA) variation and asthenozoospermia, all carried out on Tunisian men. A thorough assessment of these articles reveals that all five studies were carried out on virtually the same cohort of patients, although this information was concealed by the authors. Thus, the results were ‘sliced’ in order to unjustifiably maximize the number of publications. In addition, a phylogenetic analysis of their data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…The mtDNA rearrangement has been stated in asthenozoospermic patients [ 49 ]. The mtDNA variation has been established in the framework of various multifactorial diseases [ 23 , 50 , 51 ]. While mitochondrial mutations and their correlation to male infertility have been broadly investigated, there are still contradictions in data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mtDNA rearrangement has been stated in asthenozoospermic patients [ 49 ]. The mtDNA variation has been established in the framework of various multifactorial diseases [ 23 , 50 , 51 ]. While mitochondrial mutations and their correlation to male infertility have been broadly investigated, there are still contradictions in data.…”
Section: Discussionmentioning
confidence: 99%
“…Most SNPs are situated in non-coding regions of the genome and have no direct identified impact on the phenotype of an individual, but their character till now stays elusive, and liable on where SNPs happen; it might have unlike consequences at the phenotypic level [22]. Many studies reported that there is an association between the presence of mitochondrial DNA (mtDNA) variation and infertility in the Tunisian [23], Jordanian [24], and Iranian [25] populations.…”
Section: Introductionmentioning
confidence: 99%